Risiko Obesitas Efek Pengobatan Hipertiroid pada Pasien Hipertiroid - Paramita, Fajrinandetya; Widyawati, Ika Yuni; Pratiwi, Ika Nur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the risk of obesity and the effects of hyperthyroid treatment in hyperthyroid patients. The research method used is a systematic review through electronic databases and websites, namely ScienceDirect, Pubmed and Wiley Online Library. The research results showed that of the 7 research articles, 4 articles reported that hyperthyroidism treatment had an effect on the body, one of which was weight gain due to the disease. This needs to be controlled so that you don't become obese. There are articles stating that there is a lack of information about treatment options and their long-term consequences so that patients have no mechanism to predict these potential effects, namely weight gain that will lead to obesity. In conclusion, hyperthyroid patients undergoing treatment need to be given information about the drug therapy they are undergoing in order to reduce/avoid unwanted side effects, namely obesity. Keywords: Hyperthyroid, Medication, Obesity, Obesity Risk, Thyroid Disease